UPAYA KESEHATAN ANAK USIA DINI: PENCEGAHAN STUNTING MELALUI PRAKTIK PHBS TK SANTA MARIA FATIMAH MERAUKE - Day, Wa Ode Siti Hamsinah; Sulistyowati, Retno Wuri; Harmawati, Diah (LPPM Universitas Flores, 2024)
The service aims to create a more conducive environment for Kindergarten Santa Maria Fatimah Merauke to implement early childhood health programs and prevent stunting. The methods used through the planning stages include identifying health problems to be addressed, analysing community needs, and formulating specific goals and steps to achieve them. The implementation stages include holding PHBS training for teachers and parents and health education for children. The evaluation stage involves collecting data on community knowledge, attitudes and behaviour regarding PHBS and health indicators such as children's nutritional status. The results of this PKM activity are a real example of the synergy between academics and the community in creating a healthy and clean environment. Musamus University is committed to continuing to support programs that benefit society, especially in health and education. Conclusion: The Community Partnership Service (PKM) Clean and Healthy Living Behavior (PHBS) activities carried out at the Santa Maria Fatimah Merauke Kindergarten have achieved their main objective, namely, increasing the understanding and practice of PHBS among teachers and students.